The laboratory of Industrial Hygiene of the Clinica del Lavoro of Milan: a direct testimony - Foà, Vito (La Medicina del Lavoro, 2019)
Vito Foà started working at the industrial hygiene laboratory of the Clinica del Lavoro of Milan in 1958 and was involved in occupational toxicology. In 1977 he was appointed as director of the department of occupational toxicology and industrial hygiene. Through his direct testimony,some significant episodes of fifty years of the life of the laboratory are reported.